Correction to: What has been the progress in addressing financial risk in Uganda? Analysis of catastrophe and impoverishment due to health payments - Brendan Kwesiga; Tom Aliti; Pamela Nabukhonzo; Susan Najuko; Peter Byawaka; Justine Hsu; John E. Ataguba; Grace Kabaniha (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.